2016
DOI: 10.1016/j.cmi.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Universal influenza vaccines: a realistic option?

Abstract: The extensive antigenic drift displayed by seasonal influenza viruses and the risk of pandemics caused by newly emerging antigenically distinct influenza A viruses of novel subtypes has raised considerable interest in the development of so-called universal influenza vaccines. We review options for the development of universal flu vaccines and discuss progress that has been made recently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 77 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…Despite seasonal vaccination, influenza virus infection remains associated with high morbidity and mortality rates (Simonsen, 1999). This is due to continuous antigenic changes in the surface glycoproteins of influenza virus strains, which reduce the effectiveness of vaccination (de Vries et al, 2016;Webster and Govorkova, 2014). Antiviral drugs can be used to treat patients with severe influenza virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…Despite seasonal vaccination, influenza virus infection remains associated with high morbidity and mortality rates (Simonsen, 1999). This is due to continuous antigenic changes in the surface glycoproteins of influenza virus strains, which reduce the effectiveness of vaccination (de Vries et al, 2016;Webster and Govorkova, 2014). Antiviral drugs can be used to treat patients with severe influenza virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…These cells are induced by natural infection but are induced V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 190: [19][20][21][22][23][24][25][26][27][28] inefficiently by inactivated influenza vaccines (reviewed in [11]) [12][13][14]. These cells are induced by natural infection but are induced V C 2017 British Society for Immunology, Clinical and Experimental Immunology, 190: [19][20][21][22][23][24][25][26][27][28] inefficiently by inactivated influenza vaccines (reviewed in [11]) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that cross-reactive virusspecific CD8 1 cytotoxic T cells contribute to reduction of disease duration and severity after infection with a heterologous influenza virus [12,15]. Thus, the development of vaccines that induce broadly protective HA stalk-specific antibodies and/or cellular immune responses against conserved proteins such as NP or M1 is highly desirable and is listed high on the research agenda (reviewed in [21][22][23]). Thus, the development of vaccines that induce broadly protective HA stalk-specific antibodies and/or cellular immune responses against conserved proteins such as NP or M1 is highly desirable and is listed high on the research agenda (reviewed in [21][22][23]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the 'stalk' supporting the binding site is relatively well conserved. 3,4 "Recent advances in understanding how to preserve the structure of the stem antigen in the vaccine suggests that a universal vaccine for flu is a realistic prospect," says Dr Drury. "All being well, a candidate vaccine could be available in 10 to 15 years.…”
Section: Mark Greenermentioning
confidence: 99%